Statistical Analyses and the "Laws" of Price - Ezekiel, Mordecai (Quarterly Journal of Economics, 1928)
Economists have been skeptical as to the real significance of statistical price analyses. Simplified assumptions as to nature of price determination are partly responsible, 201. — Marshall's treatment was nearer to the concrete facts, 202. — Definition of the market in time and space has an important bearing upon the meaning of the data, 203. — Actual events represent constant flux, not successive static periods, 203. — Statistics can reveal only current adjustments, not final equilibria, 203. — The type of the adjustment varies with the length of the period, 204. — The prices which directly affect production and consumption are frequently not the central market prices, 205; and non-economic factors also are involved, 206. — A curve of supply-and-price may be determined from observations in successive intervals, 207; even if demand is changing, 208. — The curve of supply-and-price is not the theoretical demand curve, 214; since reservation demands by producers may be regarded either as a demand-schedule or a supply-schedule, 215. — With regard to a price fixed by total supply, reservation demands are part of the demand schedule, 215. — But this schedule may be resolved into its components by proper statistical analyses, 216. — This involves determination (a) of the effect of price upon supply, and (b) of the effect of price upon storage, consumption, and withholdings, 217. — Price also has an effect upon subsequent production, 219. — Such changes in production are usually more important than immediate adjustments of supply to price, 220. — This is true even of durable goods, 221. — Statistical measurement of the effect of price upon production illustrated, 222. — Statistical measurements of economic reactions do not yield absolute laws, 223. — This analysis refutes some previous criticisms of the logic of statistical price studies, 224, and of the methods, 225; and indicates the statistical cautions needed to give reliable results, 226.